Sending mixed signals: Cilia-dependent signaling during development and disease - Elliott, Kelsey H. (Dev Biol, 2018)
Molecular signals are the guiding force of development, imparting direction upon cells to divide, migrate, differentiate, etc. The mechanisms by which a cell can receive and transduce these signals into measurable actions remains a ‘black box’ in developmental biology. Primary cilia are ubiquitous, microtubule-based organelles that dynamically extend from a cell to receive and process molecular and mechanical signaling cues. In the last decade, this organelle has become increasingly intriguing to the research community due to its ability to act as a cellular antenna, receive and transduce molecular stimuli, and initiate a cellular response. In this review, we discuss the structure of primary cilia, emphasizing how the ciliary components contribute to the transduction of signaling pathways. Furthermore, we address how the cilium integrates these signals and conveys them into cellular processes such as proliferation, migration and tissue patterning. Gaining a deeper understanding of the mechanisms used by primary cilia to receive and integrate molecular signals is essential, as it opens the door for the identification of therapeutic targets within the cilium that could alleviate pathological conditions brought on by aberrant molecular signaling.